2017
DOI: 10.1634/theoncologist.2017-0085
|View full text |Cite
|
Sign up to set email alerts
|

Are Disagreements in Caregiver and Patient Assessment of Patient Health Associated with Increased Caregiver Burden in Caregivers of Older Adults with Cancer?

Abstract: Cancer‐related therapy is increasingly administered in the outpatient setting, resulting in increased dependence on caregivers suggest to provide physical and emotional support to patients. This article describes differences in patient versus caregiver assessments of patient health, considering caregiver perceptions of the patient's health and abilities compared to that reported by the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 47 publications
1
24
0
2
Order By: Relevance
“…30 Our descriptive results are similar to previous studies. 7,31,32 Hsu et al 33 found that in 100 patients aged 65 years and older (70% with advanced cancer) and their caregivers, caregivers were mostly female (73%) and spouses (68%); 79% lived with the patient. Jones et al 32 found that in 76 caregivers of older patients with cancer, 19.1% and 23.6% reported moderate or greater anxiety and depression, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…30 Our descriptive results are similar to previous studies. 7,31,32 Hsu et al 33 found that in 100 patients aged 65 years and older (70% with advanced cancer) and their caregivers, caregivers were mostly female (73%) and spouses (68%); 79% lived with the patient. Jones et al 32 found that in 76 caregivers of older patients with cancer, 19.1% and 23.6% reported moderate or greater anxiety and depression, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A higher carer burden was also associated with patient’s physical and psychological symptom burden. The causes of caregiver burden are complicated, but the literature reports a stronger association between burden and patient’s physical care needs, social networks and information needs than symptoms 29 30. There has been no previous reported association between Zarit burden score and symptoms reported on the MSAS-SF.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger correlation was found using the Hamilton Anxiety and Depression Rating Scales (HARS, HDRS), MOS-Physical Function, CSI and Zarit Caregiver Burden Interview (ZBI). Hsu et al (29) and Hu et al (30) reported higher correlations between anxiety and caregiving stress (r = 0.774, p < 0.001), depression and caregiving stress (r = 0.718, p < 0.001), and physical dysfunction and caregiving stress (p < 0.05) in family caregivers of adult patients with cancer and stroke. Understanding the direct impact of caregivers' health on the levels of caregiving stress is another important result.…”
Section: Discussionmentioning
confidence: 95%